1178 J, 527 nm near diffraction limited laser based on a complete closed-loop adaptive optics controlled off-axis multi-pass amplification laser system. (19th May 2021) - Wang, Deen; Zhang, Xin; Dai, Wanjun; Yang, Ying; Deng, Xuewei; Chen, Lin; Xie, Xudong; Hu, Dongxia; Jing, Feng; Yang, Zeping; Yuan, Qiang; Wei, Xiaofeng; et al.
Abstract: A 1178 J near diffraction limited 527 nm laser is realized in a complete closed-loop adaptive optics (AO) controlled off-axis multi-pass amplification laser system. Generated from a fiber laser and amplified by the pre-amplifier and the main amplifier, a 1053 nm laser beam with the energy of 1900 J is obtained and converted into a 527 nm laser beam by a KDP crystal with 62% conversion efficiency, 1178 J and beam quality of 7.93 times the diffraction limit (DL). By using a complete closed-loop AO configuration, the static and dynamic wavefront distortions of the laser system are measured and compensated. After correction, the diameter of the circle enclosing 80% energy is improved remarkably from 7.93DL to 1.29DL. The focal spot is highly concentrated and the 1178 J, 527 nm near diffraction limited laser is achieved.